Effect of a refined nursing model based on two-way nursing quality feedback on the postoperative mental resilience of patients with facial vascular malformation (双向质量反馈护理模式对颜面部血管畸形患者心理弹性的影响) - BAO Lili (鲍丽丽); QI Jiaxin (齐加新) (Association of Integrative Nursing, 2022)
Objective To evaluate the effect of a refined nursing model based on two-way nursing quality feedback on the postoperative mental resilience of patients with facial vascular malformation. Methods A total of 165 patients with facial vascular malformation were randomly divided into control group (n = 82) and study group (n = 83). Routine nursing was used in the control group, while two-way quality feedback nursing was used in the study group. The levels of mental resilience by Connor-Davidson Resilience Scale (CD-RISC), chronic disease stigma by Stigma Scale for Chronic Illness (SSCI) and patient satisfaction by self-made questionnaire were compared between the two groups. Results The score of CD-RISC in the study group was significantly higher than that in the control group (81. 73±2. 48 vs. 64. 15±3. 88, P＜0. 01). The score of SSCI in the study group was lower than that in the control group (44. 88±5. 68 vs. 69. 14±6. 92, P＜0. 01). The score of satisfaction evaluation in the study was higher than that of the control group (95. 01±4. 05 vs. 80. 49±6. 32, P＜0. 01). Conclusion In facial vascular malformation patients, two-way quality feedback nursing model can effectively improve the level of mental resilience, reduce the stigma of chronic illness, and improve patients' satisfaction, which is worthy of clinical application and promotion. (目的 探讨双向质量反馈护理模式对颜面部血管畸形患者心理弹性的影响。方法 选取颜面部血管畸形患者165例, 随机分为对照组82例和研究组83例。对照组运用科室常规护理, 研究组在常规护理基础上运用双向质量反馈护理模式。采用采用心理弹性量表(CD-RISC)评估患者心理弹性水平, 采用慢性疾病病耻感量表(SSCI)评估患者病耻感, 评价护理满意度。结果 研究组CD-RISC量表评分(81. 73±2. 48)分, 高于对照组的(64. 15±3. 88)分, 差异有统计学意义(P＜0. 01)。研究组SSCI量表评分(44. 88±5. 68)分, 低于对照组的(69. 14±6. 92)分, 差异有统计学意义(P＜0. 01)。研究组满意度评分为(95. 01±4. 05)分, 高于对照组的(80. 49±6. 32)分, 差异有统计学意义(P＜0. 01)。结论 采用双向质量反馈护理模式可有效提高患者心理弹性水平, 降低病耻感, 缓解患者疾病痛苦, 提高患者满意度。)